A copper-clad plate resin with high peel strength and a preparation method thereof
Patent Information
- Application Number
- CN202611288612.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]树脂基体改性方面,现有方案多采用橡胶弹性体、热塑性树脂共混增韧,或引入极性官能团提升树脂活性,但均存在难以平衡的性能矛盾:橡胶增韧体系往往会降低树脂的耐热性与介电性能,无法适配高频高耐热场景;热塑性树脂共混易出现相容性问题,固化过程中发生微观相分离,反而在基体内形成界面缺陷,削弱整体力学性能与界面结合稳定性;单一引入极性基团的改性方式对剥离强度提升幅度有限,且难以改善湿热环境下的界面劣化问题
1、本发明采用N-苯基马来酰亚胺、4-乙烯基苯甲酸与甲基丙烯酸异癸酯共聚制备的三元共聚物作为改性组分,三类结构单元功能互补:N-苯基马来酰亚胺单元含刚性酰亚胺环与芳环结构,赋予共聚物优异的耐热稳定性,固化后可维持树脂体系较高的玻璃化转变温度,解决了传统橡胶类增韧组分易导致树脂耐热性大幅下降的问题;4-乙烯基苯甲酸单元引入活性羧基官能团,一方面可在固化过程中与环氧树脂的环氧基团发生开环反应,使共聚物与环氧基体形成共价键连接,从根本上避免物理共混体系易出现的相分离缺陷,保障树脂基体力学性能的均一性;另一方面,羧基可与铜箔表面活性位点形成化学键合作用,构建化学结合与机械互锁协同作用的界面结合模式,显著提升铜箔常温剥离强度。甲基丙烯酸异癸酯单元带有长侧链烷基结构,可提供良好的链段柔顺性,有效分散界面集中应力,缓冲铜箔与树脂基体热膨胀系数差异带来的热应力失配,降低热循环工况下的界面开裂风险,同时该单元极性较低,不会过度劣化树脂体系的介电性能,可适配高频应用场景的需求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of resin materials technology, and in particular to a high peel strength copper-clad laminate resin and its preparation method. Background Technology
[0002] Copper-clad laminates (CCLs), as the core substrate of printed circuit boards (PCBs), bear the core functions of circuit carrying, electrical insulation, and structural support. Their performance directly determines the signal transmission stability and long-term service reliability of electronic devices. With the rapid development of 5G / 6G communications, high-density integrated circuits, automotive electronics, and aerospace, electronic devices are continuously iterating towards high frequency, high speed, high integration, and high reliability, placing more stringent requirements on the comprehensive performance of the CCL resin matrix. Among these requirements, copper foil peel strength, as a core indicator for measuring the interfacial bonding reliability of CCLs, has become a key research focus in the industry.
[0003] Currently, epoxy resin is the mainstream resin system for copper clad laminates, occupying a wide application market due to its mature process and balanced mechanical and insulation properties. For high-frequency and high-speed applications, low-polarity resin systems such as hydrocarbon resins and polyimide are also gradually being promoted. However, existing resin systems all have significant shortcomings in peel strength performance: the interfacial bonding between traditional epoxy resin systems and copper foil relies on mechanical interlocking and limited chemical bonding, which easily leads to interfacial degradation under high temperature, high humidity, and thermal cycling conditions, resulting in a significant decrease in peel strength and making it difficult to meet the long-term service requirements of high-reliability applications; while low-polarity high-frequency special resins have weak molecular polarity and poor chemical affinity with copper foil, inherently possessing insufficient interfacial bonding strength, resulting in generally low peel strength.
[0004] To improve the peel strength of copper foil, the existing technical approaches in the industry are mainly divided into two categories: copper foil surface modification and resin matrix modification. Copper foil surface modification improves the surface roughness and the number of active sites by means of roughening treatment, plasma activation, and coupling agent coating, thereby strengthening mechanical interlocking and chemical bonding. However, this type of solution has obvious limitations in high-frequency application scenarios: low profile copper foil is a necessary condition for reducing skin loss of high-frequency signals, and excessive roughening will aggravate signal scattering and transmission loss. It is impossible to balance high-frequency performance and interfacial bonding strength. Moreover, the surface treatment process is complex and has poor batch stability, making it difficult to adapt to large-scale production.
[0005] Regarding resin matrix modification, existing solutions mostly employ rubber elastomers and thermoplastic resins for toughening, or introduce polar functional groups to enhance resin activity. However, all of these solutions present unbalanced performance contradictions: rubber toughening systems often reduce the resin's heat resistance and dielectric properties, making them unsuitable for high-frequency and high-heat-resistance scenarios; thermoplastic resin blends are prone to compatibility issues, and micro-phase separation occurs during curing, which in turn forms interface defects within the matrix, weakening the overall mechanical properties and interfacial bonding stability; and modification methods that introduce polar groups alone have limited improvement on peel strength and are difficult to improve interface degradation in humid and hot environments.
[0006] In summary, existing copper clad laminate resin systems cannot simultaneously meet the multiple requirements of high frequency, low loss, high heat resistance, and high peel strength. In particular, in the case of low roughness copper foil, how to significantly improve the peel strength of copper foil under normal temperature, humid heat, and high temperature conditions without sacrificing the overall performance of the resin matrix remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the problems mentioned in the background section, this invention provides a copper-clad laminate resin with high peel strength and a method for preparing the same.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: The method for preparing high peel strength copper clad laminate resin provided by the present invention includes the following steps: S1. Preparation of terpolymer solution: Using propylene glycol methyl ether acetate as solvent, N-phenylmaleimide, 4-vinylbenzoic acid and isodecanyl methacrylate mixed monomers are subjected to solution free radical polymerization under nitrogen protection and the action of an initiator. After the reaction is completed, the mixture is cooled and discharged to obtain the terpolymer solution.
[0009] In some embodiments, in step S1, the total mass of the mixed monomers is 100 parts by mass, of which N-phenylmaleimide is 26-28 parts by mass, 4-vinylbenzoic acid is 19-21 parts by mass, and isodecanyl methacrylate is 52-54 parts by mass.
[0010] In some embodiments, in step S1, the amount of propylene glycol methyl ether acetate is 140-160 parts by weight; the initiator is azobisisobutyronitrile, and the total amount is 1.2%-1.4% of the total mass of the mixed monomers, added in two batches. Further, the initial initiator addition is 70%-80% of the total initiator mass, and the remaining 20%-30% of the initiator is added after the first stage of the heat-preserving reaction is completed.
[0011] In some embodiments, the polymerization reaction in step S1 specifically involves: heating the system to 73-77°C, simultaneously adding the mixed monomer and initiator solution dropwise for 2.8-3.2 hours, with temperature fluctuations ≤ ±2°C during the dropwise addition; after the dropwise addition is completed, maintaining the temperature at 74-76°C for 4.5-5.5 hours, adding the remaining initiator, and then heating to 78-82°C for another 1.5-2.5 hours. Further, the mixed monomer and initiator solution are added simultaneously at a uniform rate, with the dropwise line inserted below the reaction liquid surface; after the second stage of the heat preservation reaction is completed, a sample is taken to check if the monomer conversion rate is ≥ 98%, and then the cooling and discharge operation is performed.
[0012] In some embodiments, in step S1, the initiator solution is prepared by dissolving the initiator in 30-40 parts by weight of propylene glycol methyl ether acetate; the solid content of the resulting terpolymer solution is 43%-47%.
[0013] In some embodiments, in step S1, nitrogen gas is introduced into the reactor for 15-25 minutes to replace the air in the reactor before the reaction begins. After the oxygen content of the system drops below 100 ppm, the heating program is started. The polymerization reaction is maintained in a slightly positive nitrogen environment, with the gauge pressure controlled at 0.01-0.03 MPa. The stirring speed is kept constant at 180-220 r / min during the polymerization reaction. After the reaction is completed, the mixture is cooled to 30-40℃ and discharged.
[0014] S2. Preparation of resin solution: Mix bisphenol A type epoxy resin with the terpolymer solution obtained in step S1 evenly, add linear phenolic curing agent and stir to disperse, then add surface modified nano silica for shear dispersion, and finally add curing accelerator and vacuum degassing to obtain copper clad laminate resin solution.
[0015] In some embodiments, in step S2, based on the mass parts of solid content, the bisphenol A type epoxy resin is 65-75 parts, the terpolymer is 25-35 parts, the linear phenolic curing agent is 37-41 parts, the surface-modified nano silica is 28-32 parts, and the curing accelerator is 0.3-0.5 parts.
[0016] In some embodiments, the bisphenol A type epoxy resin is E-51 type bisphenol A type epoxy resin with an epoxy value of 0.48-0.54 eq / 100g; the linear phenolic curing agent has a hydroxymethyl content of 8%-12% and a ring and ball softening point of 80-95℃.
[0017] In some embodiments, in step S2, the curing accelerator is selected from one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, and benzyldimethylamine.
[0018] In some embodiments, in step S2, the surface-modified nano-silica is nano-silica modified with γ-glycidyl etheroxypropyltrimethoxysilane, with an average particle size of 0.4-0.6 μm. Further, the silane coupling agent grafting rate of the surface-modified nano-silica is 1.5%-2.5%, and the specific surface area is 180-220 m². 2 / g.
[0019] In some embodiments, in step S2, the surface-modified nano-silica is added in three batches. After each batch is added, it is sheared and dispersed at a speed of 1200-1500 r / min for 13-17 min. After all the materials are added, shearing and dispersion continues for 35-45 min. Furthermore, during the shearing and dispersion process, the system temperature is controlled at 35-45℃ throughout to avoid local overheating that could lead to resin pre-curing.
[0020] In some embodiments, in step S2, methyl ethyl ketone is added to adjust the initial solid content of the system to 50%-55%, and the mixture is stirred at 35-45°C and 600-800 r / min for 25-35 min; after adding the linear phenolic curing agent, the mixture is stirred at the same speed for 18-22 min; after adding the curing accelerator, the mixture is stirred at 400-600 r / min for 8-12 min, and then allowed to stand and degas at a vacuum of (-0.090)-(-0.095) MPa for 12-18 min, resulting in a resin solution with a solid content of 58%-62%.
[0021] According to another aspect of the present invention, a high peel strength copper-clad laminate is also provided, which is prepared by impregnating a copper-clad laminate resin solution obtained by the above preparation method into a prepreg and then vacuum laminating and curing it.
[0022] In some embodiments, the resin impregnation process for preparing the prepreg involves: immersing electronic-grade glass cloth in copper-clad laminate resin solution at a flow rate of 2-4 m / min, followed by drying in a three-stage oven with oven temperatures set sequentially along the material flow direction to 110-130℃, 140-160℃, and 150-170℃. The resulting prepreg has a gelation time of 120-180 s and a resin content of 45%-55%.
[0023] In some embodiments, the vacuum lamination curing specifically involves: arranging the prepreg and copper foil in a laminated structure and placing them in a vacuum hot press; first, evacuating the system to a vacuum degree ≤ -0.095 MPa; then applying a molding pressure of 1.5-2.5 MPa; and curing in stages: holding at 120℃ for 25-35 min, at 150℃ for 55-65 min, and at 180℃ for 85-95 min; after curing, allowing the furnace to cool naturally to below 60℃ before releasing the pressure and discharging the material.
[0024] The beneficial effects of this invention are: 1. This invention uses a terpolymer prepared by copolymerizing N-phenylmaleimide, 4-vinylbenzoic acid, and isodecanyl methacrylate as the modifying component. The three structural units complement each other: the N-phenylmaleimide unit contains a rigid imide ring and an aromatic ring structure, which endows the copolymer with excellent heat resistance and can maintain a high glass transition temperature of the resin system after curing, solving the problem that traditional rubber toughening components can easily lead to a significant decrease in the heat resistance of the resin; the 4-vinylbenzoic acid unit introduces an active carboxyl functional group, which can undergo a ring-opening reaction with the epoxy group of the epoxy resin during the curing process, so that the copolymer and the epoxy body form a covalent bond, fundamentally avoiding the phase separation defects that are prone to occur in physical blending systems and ensuring the uniformity of the mechanical properties of the resin matrix; on the other hand, the carboxyl group can form a chemical bond with the active sites on the surface of the copper foil, constructing an interfacial bonding mode with synergistic effect of chemical bonding and mechanical interlocking, which significantly improves the room temperature peel strength of the copper foil. The isodecyl methacrylate unit has a long side-chain alkyl structure, which can provide good chain flexibility, effectively disperse interfacial stress concentration, buffer the thermal stress mismatch caused by the difference in thermal expansion coefficients between copper foil and resin matrix, reduce the risk of interfacial cracking under thermal cycling conditions, and at the same time, the unit has low polarity, which will not excessively degrade the dielectric properties of the resin system, making it suitable for the needs of high-frequency application scenarios.
[0025] 2. This invention uses γ-glycidyl etheroxypropyltrimethoxysilane-modified nano-silica as a functional filler. The epoxy functional groups grafted on the filler surface can participate in the epoxy resin curing and crosslinking reaction, realizing the chemical bonding between the filler and the resin matrix, effectively improving the compatibility between the filler and the matrix, and avoiding internal defects in the matrix caused by filler agglomeration. The rigid silica filler can improve the elastic modulus and dimensional stability of the resin matrix, further reduce the difference in thermal expansion coefficients between the resin and the copper foil, and reduce the accumulation of interfacial stress during long-term service. At the same time, the filler can extend the diffusion path of water vapor in the resin, reduce the penetration rate of water vapor to the resin body and the copper foil interface, inhibit the interfacial hydrolysis and deterioration under humid and hot conditions, significantly improve the peel strength retention rate after high temperature and high humidity aging, and ensure the long-term service reliability of the copper clad laminate.
[0026] 3. This invention improves interfacial bonding strength through molecular modification of the resin matrix, eliminating the need for high-roughness coarsening of the copper foil. It is adaptable to the fabrication of copper-clad laminates using low-profile copper foil, effectively avoiding the increased skin loss of high-frequency signals caused by high copper foil roughness. This solves the core contradiction in existing technologies where high-frequency, low-loss performance and high peel strength are difficult to achieve simultaneously. The overall fabrication process is compatible with existing industrial production processes for copper-clad laminates, with controllable process parameters, good batch stability, and significant industrial application value. Detailed Implementation
[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides a method for preparing a high peel strength copper-clad laminate resin, comprising the following steps: S1. Add 110g of propylene glycol methyl ether acetate as the base solvent to the reactor. After purging the reactor with nitrogen to replace the air, start stirring and heat the system to 73℃. Weigh 26g of N-phenylmaleimide, 20g of 4-vinylbenzoic acid, and 54g of isodecanyl methacrylate, and stir to mix evenly to obtain a mixed monomer. Weigh 0.9g of azobisisobutyronitrile and dissolve it in 30g of propylene glycol methyl ether acetate to prepare an initiator solution. Add the mixed monomer and the initiator solution dropwise to the reactor simultaneously and at a uniform rate for 2.8h. During the dropwise addition, the system temperature fluctuates within ±2℃, and nitrogen protection is maintained throughout. After the dropwise addition is completed, maintain the reaction temperature at 74℃ for 4.5h. Add 0.3g of azobisisobutyronitrile, raise the temperature to 78℃, and continue the reaction for 1.5h. After the reaction is completed, cool and discharge the material to obtain a terpolymer solution.
[0030] S2. Weigh 65g of bisphenol A epoxy resin, add 81.4g of the above terpolymer solution, and then add 54g of methyl ethyl ketone to adjust the system concentration. Stir and mix at 35℃ and 600r / min for 25min. Add 37g of linear phenolic curing agent and continue stirring for 18min while maintaining the stirring speed. Then, add a total of 28g of nano-silica (average particle size 0.4μm) modified with γ-glycidoxypropyltrimethoxysilane in 3 batches. After each batch is added, shear and disperse at 1200r / min for 13min. After all the materials are added, continue shear and disperse for 35min. The system temperature is controlled at 35℃ during the dispersion process. Finally, add 0.3g of 2-methylimidazole curing accelerator and stir at 400r / min for 8min. Then, let it stand under a vacuum of -0.090MPa for 12min to remove bubbles and obtain the copper-clad laminate resin solution.
[0031] Example 2
[0032] This embodiment provides a method for preparing a high peel strength copper-clad laminate resin, comprising the following steps: S1. Add 115g of propylene glycol methyl ether acetate as the base solvent to the reactor. After purging the reactor with nitrogen to replace the air, start stirring and heat the system to 75℃. Weigh 27g of N-phenylmaleimide, 21g of 4-vinylbenzoic acid, and 52g of isodecanyl methacrylate, and stir to mix evenly to obtain a mixed monomer. Weigh 0.975g of azobisisobutyronitrile and dissolve it in 35g of propylene glycol methyl ether acetate to prepare an initiator solution. Add the mixed monomer and the initiator solution dropwise to the reactor simultaneously and at a uniform rate for 3.0h. During the dropwise addition, the system temperature fluctuates within ±2℃, and nitrogen protection is maintained throughout. After the dropwise addition is completed, maintain the reaction temperature at 75℃ for 5.0h, add 0.325g of azobisisobutyronitrile, raise the temperature to 80℃ and continue the reaction for 2.0h. After the reaction is completed, cool and discharge the material to obtain a terpolymer solution.
[0033] S2. Weigh 70g of bisphenol A epoxy resin, add 66.7g of the above terpolymer solution, and then add 56g of methyl ethyl ketone to adjust the system concentration. Stir and mix at 40℃ and 700r / min for 30min. Add 39g of linear phenolic curing agent and continue stirring at the same speed for 20min. Then add a total of 30g of nano-silica (average particle size 0.5μm) modified with γ-glycidoxypropyltrimethoxysilane in three batches. After each batch is added, shear and disperse at 1350r / min for 15min. After all the materials are added, continue shear and disperse for 40min. The system temperature is controlled at 40℃ during the dispersion process. Finally, add 0.4g of 2-ethyl-4-methylimidazolium curing accelerator and stir at 500r / min for 10min. Then let it stand under a vacuum of -0.092MPa for 15min to remove bubbles, and obtain the copper-clad laminate resin solution.
[0034] Example 3
[0035] This embodiment provides a method for preparing a high peel strength copper-clad laminate resin, comprising the following steps: S1. Add 120g of propylene glycol methyl ether acetate as the base solvent to the reactor. After purging the reactor with nitrogen to replace the air, start stirring and heat the system to 77℃. Weigh 28g of N-phenylmaleimide, 19g of 4-vinylbenzoic acid, and 53g of isodecanyl methacrylate, and stir to mix evenly to obtain a mixed monomer. Weigh 1.05g of azobisisobutyronitrile and dissolve it in 40g of propylene glycol methyl ether acetate to prepare an initiator solution. Add the mixed monomer and the initiator solution dropwise to the reactor simultaneously and at a uniform rate for 3.2h. During the dropwise addition, the system temperature fluctuates within ±2℃, and nitrogen protection is maintained throughout. After the dropwise addition is completed, maintain the reaction temperature at 76℃ for 5.5h, add 0.35g of azobisisobutyronitrile, raise the temperature to 82℃, and continue the reaction for 2.5h. After the reaction is completed, cool and discharge the material to obtain a terpolymer solution.
[0036] S2. Weigh 75g of bisphenol A epoxy resin, add 53.2g of the above terpolymer solution, and then add 54g of methyl ethyl ketone to adjust the system concentration. Stir and mix at 45℃ and 800r / min for 35min. Add 41g of linear phenolic curing agent and continue stirring at the same speed for 22min. Then add a total of 32g of nano-silica (average particle size 0.6μm) modified with γ-glycidoxypropyltrimethoxysilane in 3 batches. After each batch is added, shear and disperse at 1500r / min for 17min. After all the materials are added, continue shear and disperse for 45min. The system temperature is controlled at 45℃ during the dispersion process. Finally, add 0.5g of benzyl dimethylamine curing accelerator and stir at 600r / min for 12min. Then let it stand under a vacuum of -0.095MPa for 18min to remove bubbles and obtain copper-clad laminate resin solution.
[0037] Comparative Example 1 The difference between this comparative example and Example 2 is that no terpolymer is added, and the amount of bisphenol A epoxy resin is adjusted to 100g. The remaining components, amounts, and preparation processes are the same as in Example 2.
[0038] Comparative Example 2 The difference between this comparative example and Example 2 is that 4-vinylbenzoic acid is not added when preparing the copolymer, and the amount of isodecyl methacrylate is adjusted accordingly to maintain the total mass of the mixed monomers at 100g. The rest of the polymerization process and subsequent glue preparation parameters are the same as in Example 2.
[0039] Comparative Example 3 The difference between this comparative example and Example 2 is that N-phenylmaleimide was not added when preparing the copolymer, and the amount of isodecyl methacrylate was adjusted accordingly to maintain the total mass of the mixed monomers at 100g. The rest of the polymerization process and subsequent glue preparation parameters are the same as in Example 2.
[0040] Comparative Example 4 The difference between this comparative example and Example 2 is that the nano-silica modified with γ-glycidoxypropyltrimethoxysilane was replaced with an equal mass of unmodified ordinary nano-silica. The remaining components, amounts, and preparation processes are the same as in Example 2.
[0041] Comparative Example 5 The difference between this comparative example and Example 2 is that surface-modified nano-silica is not added, while the remaining components, amounts, and preparation processes are the same as in Example 2.
[0042] To compare and verify the effects of the core technical features of this invention, five sets of comparative examples were set up. All comparative examples were based on Example 2 with single-factor adjustments, and the remaining processes and parameters remained completely consistent. The difference between Comparative Example 1 and Example 2 was that no terpolymer was added, and the amount of bisphenol A epoxy resin was adjusted to 100g accordingly; the difference between Comparative Example 2 and Example 2 was that 4-vinylbenzoic acid was not added when preparing the terpolymer, and the amount of isodecyl methacrylate was adjusted accordingly to maintain the total mass of the mixed monomers at 100g; the difference between Comparative Example 3 and Example 2 was that N-phenylmaleimide was not added when preparing the terpolymer, and the amount of isodecyl methacrylate was adjusted accordingly to maintain the total mass of the mixed monomers at 100g; the difference between Comparative Example 4 and Example 2 was that the nano-silica modified with γ-glycidoxypropyltrimethoxysilane was replaced with an equal mass of unmodified ordinary nano-silica; the difference between Comparative Example 5 and Example 2 was that no surface-modified nano-silica was added.
[0043] All resin solutions prepared in the examples and comparative examples were processed using a completely uniform process to prepare copper-clad laminate samples, in order to eliminate the interference of process differences on performance test results. In the prepreg preparation stage, each group of resin solutions was poured into the glue tank of a vertical impregnation machine. 2116 electronic-grade glass cloth was used as the reinforcing substrate, and the impregnation speed was controlled at 3 m / min. After the glass cloth passed through the glue tank at a uniform speed to complete the glue application, it entered a three-stage hot air oven for drying. The oven temperature along the material feeding direction was set sequentially to 120℃, 150℃, and 160℃. After drying, the prepreg was wound up to obtain the prepreg. During the preparation process, the resin content of all groups of prepregs was controlled to be 50% ± 2%, and the gelation time was 150 s ± 10 s, by fine-tuning the speed and glue concentration. In the copper clad laminate stage, eight corresponding prepreg sheets were neatly stacked in each group, and one 1oz low-profile electrolytic copper foil was attached to each of the top and bottom surfaces. The whole assembly was placed in a vacuum hot press for curing and molding. The curing process was uniformly set as follows: first, vacuum was drawn to a system vacuum degree ≤ -0.095MPa, then a molding pressure of 2MPa was applied, and a segmented heating and holding mode was adopted: 120℃ for 30min, 150℃ for 60min, and 180℃ for 90min. After curing, the furnace was naturally cooled to below 60℃, and the pressure was released to obtain copper clad laminate samples with a thickness of about 1.6mm. Three samples were prepared in parallel for each group for subsequent performance testing.
[0044] All performance tests were conducted under standard conditions of 25℃ room temperature and 50% relative humidity. The average of three parallel samples for each test group was taken as the final result, with the deviation of parallel sample tests controlled within 5%. The room temperature copper foil peel strength test was performed according to IPC-TM-650 2.4.8 standard. The copper-clad laminate was cut into strips with a width of 10mm, and a 90° copper foil peel test was performed using a universal testing machine. The tensile rate was set to 50mm / min, and the average load of the stable peeled section was recorded, and the room temperature peel strength was calculated. The peel strength test after damp heat aging was performed using a high-pressure steam test chamber. The cut 10mm wide samples were placed at 121℃, 100% relative humidity, and 0.2MPa for 24 hours. After removal, the surface moisture was wiped dry with filter paper, and the test was immediately performed according to the room temperature peel strength test method. The peel strength retention rate was calculated, which is the ratio of the aging peel strength to the room temperature peel strength multiplied by 100%. Glass transition temperature (GLT) testing was performed according to IPC-TM-650 2.4.25 standard, using a differential scanning calorimeter under a nitrogen atmosphere at a heating rate of 10℃ / min. The midpoint of the two heating curves was taken as the GLT of the sample to characterize the heat resistance of the resin system. Dielectric property testing was performed according to IPC-TM-650 2.5.5.9 standard, using an impedance analyzer at a frequency of 1GHz to test the dielectric constant and dielectric loss factor of the copper-clad laminate substrate to characterize the high-frequency adaptability of the resin system. Water absorption testing was performed according to IPC-TM-650 2.6.2.1 standard. After drying the substrate sample (with copper foil removed) to constant weight, the initial mass was recorded. The sample was then immersed in deionized water at 25℃ for 24 hours, dried, and weighed again. The water absorption rate was calculated from the difference in mass.
[0045] The results are shown in Table 1: Table 1. Experimental results of different embodiments and comparative examples
[0046] Table 2. Heat resistance and dielectric properties of each group of samples
[0047] Table 3. Water absorption properties of each group of samples
[0048] As shown in Table 1, the room temperature peel strength of the copper foil in Examples 1-3 ranged from 1.87 to 2.05 N / mm. After 24 hours of humid heat aging at 121℃, the peel strength retention rate of all examples reached over 85.9%. The overall interfacial bonding performance and humid heat resistance were significantly better than all comparative examples, indicating that the copper-clad laminate resin prepared by this invention can construct a stable copper foil-resin interface, possessing both high peel strength and excellent long-term humid heat resistance. This invention obtains a terpolymer modified component by copolymerizing N-phenylmaleimide, 4-vinylbenzoic acid, and isodecanyl methacrylate. The carboxyl functional group introduced by 4-vinylbenzoic acid undergoes a ring-opening reaction with the epoxy group of the epoxy resin, allowing the copolymer to be covalently integrated into the epoxy crosslinking network, avoiding the phase separation defects that are prone to occur in physical blending systems. At the same time, the carboxyl group can form chemical bonds with the active sites on the copper foil surface, which, combined with the mechanical interlocking effect of the resin matrix, significantly increases the upper limit of interfacial bonding force. The long side-chain structure of isodecyl methacrylate can effectively disperse the concentrated stress at the interface and buffer the accumulation of interfacial stress caused by the thermal expansion mismatch between copper foil and resin. Combined with the effect of surface-modified nano silica on improving the dimensional stability of the matrix, it further enhances the long-term service stability of the interface.
[0049] Comparative Example 1, without the addition of the terpolymer, exhibited a peel strength of only 1.24 N / mm at room temperature, and a peel strength retention rate of only 61.3% after aging, showing the most significant performance degradation. This is because the bonding between the pure epoxy-phenolic curing system and the copper foil relies solely on limited mechanical interlocking, resulting in a low intrinsic upper limit of interfacial bonding strength. Furthermore, the interface is prone to hydrolytic degradation under humid and hot conditions, making it impossible to maintain a stable bonding state.
[0050] Comparative Example 2 omitted the 4-vinylbenzoic acid component in the terpolymer, resulting in a room temperature peel strength of only 1.38 N / mm and a retention rate of only 64.5% after damp heat aging. This is because the lack of active carboxyl functional groups prevents the copolymer from forming covalent bonds with the epoxy matrix, leading to decreased system compatibility and interfacial defects. Furthermore, the copolymer cannot form chemical bonds with the copper foil surface, and the interfacial bonding remains primarily mechanical interlocking. Consequently, both peel strength and damp heat resistance are significantly reduced.
[0051] Comparative Example 3 omitted the N-phenylmaleimide component in the terpolymer, resulting in a room temperature peel strength of only 1.71 N / mm and a retention rate of only 71.3% after damp heat aging. This is because the lack of rigid imide structure reduces the heat resistance of the resin system, increases the coefficient of thermal expansion, exacerbates the thermal stress mismatch between the copper foil and the resin, and impairs the interfacial bonding stability. However, because the system still retains the chemical bonding of carboxyl functional groups, its performance is still better than that of Comparative Example 2, which did not introduce carboxyl groups.
[0052] Comparative Example 4 replaced the surface-modified nano-silica with unmodified ordinary nano-silica, and Comparative Example 5 did not add nano-silica. The peel strength and moisture retention rate of both were significantly lower than those of the examples. This is because unmodified silica has poor compatibility with the resin matrix, easily agglomerates to form internal defects in the matrix, weakening mechanical continuity and interfacial bonding. Without filler, the matrix dimensional stability is insufficient, and the lack of filler to block moisture makes it easier for moisture to penetrate to the interface and cause deterioration in a humid environment. Therefore, the moisture resistance performance of both examples decreased significantly.
[0053] As shown in Table 2, the glass transition temperatures of Examples 1-3 were maintained in the range of 142.3-146.8℃, while the dielectric constant remained stable at 3.98-4.05 and the dielectric loss factor was below 0.018 at 1GHz. This demonstrates that the resin system of this invention achieves a synergistic balance of multiple properties while maintaining high peel strength, excellent heat resistance, and high-frequency compatibility. This invention utilizes the rigid imide ring and aromatic ring structure of the N-phenylmaleimide unit in the terpolymer, which, after being incorporated into the crosslinking network, significantly improves the system's heat resistance and maintains a high glass transition temperature. The low-polarity long side-chain alkyl group of the isodecanyl methacrylate unit effectively reduces the overall polarity of the system, offsetting some of the negative impact of polar functional groups on dielectric properties and ensuring the resin's high-frequency application potential. Surface-modified nano-silica, covalently bonded to the matrix, further restricts the thermal motion of resin segments, aiding in improved heat resistance without introducing excessive interfacial polarization loss.
[0054] Comparative Example 1, without the addition of the terpolymer, had a glass transition temperature of only 128.5℃, the highest dielectric constant and dielectric loss among all groups, and the worst heat resistance and high-frequency performance. This is because the pure epoxy-phenolic crosslinking network lacks rigidity and has a high content of polar groups, making it unable to simultaneously meet the requirements of high heat resistance and low dielectric strength.
[0055] The heat resistance of Comparative Examples 2 and 3 was significantly lower than that of the Example. Comparative Example 3 had a glass transition temperature of only 124.7°C. Although its dielectric properties were similar to those of the Example, its heat resistance was severely compromised. This is because Comparative Example 2 lacked a carboxyl-involved crosslinking reaction, resulting in a decrease in the overall crosslinking density and limited improvement in heat resistance. Comparative Example 3 removed N-phenylmaleimide, leading to a lack of rigid structural support in the crosslinking network, a significant decrease in chain segment movement resistance, and a marked reduction in heat resistance, making it unsuitable for high-reliability applications.
[0056] The heat resistance of Comparative Examples 4 and 5 was lower than that of the Example, while the dielectric properties were not significantly different from those of the Example. This is because the unmodified silica has a weak bond with the matrix and cannot effectively restrict the thermal movement of the resin chain segments. The filler-free system lacks the support of rigid fillers, thus the heat resistance of both decreased. However, the fillers have a limited impact on the overall polarity of the system, so the dielectric properties fluctuate less.
[0057] As shown in Table 3, the water absorption rates of Examples 1-3 are all below 0.23%, significantly lower than all comparative examples, indicating that the resin system of this invention possesses excellent water permeability resistance, further ensuring performance stability under humid and hot conditions. This invention enhances the density of the crosslinked network through the full reaction of the carboxyl groups of the terpolymer with epoxy, reducing the free volume permeable by water molecules; simultaneously, the uniformly dispersed surface-modified nano-silica extends the diffusion path of water vapor within the resin. The synergistic effect of these two factors effectively reduces the water absorption rate of the system.
[0058] Comparative Example 1 exhibited the highest water absorption rate of 0.38%, the highest among all groups. This is because the cross-linked network of the pure epoxy system lacks density, resulting in a high proportion of free volume, allowing water molecules to more easily penetrate into the matrix. Comparative Examples 2 and 3 showed significantly higher water absorption rates than the Example. This is because structural defects in the copolymer led to a decrease in the cross-linking density and an increase in internal network voids, providing more channels for water vapor penetration. Comparative Examples 4 and 5 also had higher water absorption rates than the Example. In these examples, the interfacial gaps between the unmodified silica and the matrix formed water vapor penetration pathways, and the unfilled systems lacked the barrier and extension effect of the filler, thus resulting in decreased water penetration resistance.
[0059] In summary, this invention achieves functional complementarity of interfacial bonding, heat resistance, and low polarity through a terpolymer constructed from N-phenylmaleimide, 4-vinylbenzoic acid, and isodecanyl methacrylate. Combined with the reinforcing barrier effect of surface-modified nano-silica, it significantly improves the copper foil peel strength and wet heat aging performance retention rate of copper clad laminates while maintaining excellent dielectric properties and heat resistance stability.
[0060] In the description of this specification, the reference to terms such as "embodiment," "various embodiments," etc., indicates that a specific feature, structure, material, or characteristic described in connection with that embodiment or preparation example is included in at least one embodiment of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments.
[0061] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a high peel strength copper-clad laminate resin, characterized in that, Includes the following steps: S1. Using propylene glycol methyl ether acetate as solvent, under nitrogen protection and the action of an initiator, a mixture of monomers including N-phenylmaleimide, 4-vinylbenzoic acid and isodecyl methacrylate is subjected to solution free radical polymerization. After the reaction is completed, the mixture is cooled and discharged to obtain a terpolymer solution. S2. Mix the bisphenol A type epoxy resin with the terpolymer solution obtained in step S1 evenly, add linear phenolic curing agent and stir to disperse, then add surface modified nano silica for shear dispersion, and finally add curing accelerator and vacuum degas to obtain copper clad laminate resin solution.
2. The preparation method according to claim 1, characterized in that, In step S1, the total mass of the mixed monomers is 100 parts by mass, of which N-phenylmaleimide is 26-28 parts by mass, 4-vinylbenzoic acid is 19-21 parts by mass, and isodecanyl methacrylate is 52-54 parts by mass.
3. The preparation method according to claim 1, characterized in that, In step S1, the amount of propylene glycol methyl ether acetate is 140-160 parts by mass; the initiator is azobisisobutyronitrile, and the total amount is 1.2%-1.4% of the total mass of the mixed monomers, added in two doses.
4. The preparation method according to claim 1, characterized in that, The polymerization reaction in step S1 is as follows: the system is heated to 73-77℃, and the mixed monomer and initiator solution are added dropwise simultaneously for 2.8-3.2h. The temperature fluctuation of the system during the dropwise addition is ≤±2℃. After the dropwise addition is completed, the system is kept at 74-76℃ for 4.5-5.5h. After the remaining initiator is added, the temperature is raised to 78-82℃ and the system is kept at 78-82℃ for another 1.5-2.5h.
5. The preparation method according to claim 1, characterized in that, In step S1, the initiator solution is prepared by dissolving the initiator in 30-40 parts by mass of propylene glycol methyl ether acetate; the solid content of the resulting terpolymer solution is 43%-47%.
6. The preparation method according to claim 1, characterized in that, In step S2, based on the mass fractions calculated from the solid content, the bisphenol A epoxy resin is 65-75 parts, the terpolymer is 25-35 parts, the linear phenolic curing agent is 37-41 parts, the surface-modified nano silica is 28-32 parts, and the curing accelerator is 0.3-0.5 parts.
7. The preparation method according to claim 1, characterized in that, In step S2, the curing accelerator is selected from one or more of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, and benzyldimethylamine.
8. The preparation method according to claim 1, characterized in that, In step S2, the surface-modified nano-silica is nano-silica modified with γ-glycidyl etheroxypropyltrimethoxysilane, with an average particle size of 0.4-0.6 μm; the filler is added in 3 batches, and after each batch is added, it is sheared and dispersed at a speed of 1200-1500 r / min for 13-17 min, and after all the fillers are added, it is sheared and dispersed for another 35-45 min.
9. The preparation method according to claim 1, characterized in that, In step S2, add methyl ethyl ketone to adjust the initial solid content of the system to 50%-55%, and mix at 35-45℃ and 600-800 r / min for 25-35 min; after adding the linear phenolic curing agent, maintain the stirring speed for 18-22 min. After adding the curing accelerator, stir at 400-600 r / min for 8-12 min, then let stand for 12-18 min under a vacuum of (-0.090)-(-0.095) MPa to degas the resin. The resulting resin liquid has a solid content of 58%-62%.
10. A high peel strength copper-clad laminate, characterized in that, The copper-clad laminate resin solution obtained by any one of claims 1-9 is prepared by impregnation to form a prepreg and vacuum lamination curing.